Regional governance structures in indigenous Australia: Western Australian examples - Barcham, Manuhuia (Massey University, 2009)
The last few years have been witness to a dramatic change in indigenous affairs in Australia. This process has resulted in the disestablishment of ATSIC and a movement towards the promotion of regional governance structures for indigenous Australia. This article investigates three organisations in the Southwest of Western Australia which may form the basis of a regional governance structure. These three cases illuminate a number of generic issues that must be considered if the aim of the current shift in indigenous affairs policy is to lead to robust and successful outcomes for indigenous Australians. Issues of capacity, legitimacy and the ‘fit’ of structures to indigenous populations are of critical import to the success or failure of this process.
Keywords: Indigenous affairs; Australia; Case studies; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy